Fetures of increase of productivity of welding an consumable electrode in gas shielded at the expense of arch activation - Савицкий, А. М.; Савицкий, М. М.; Шкрабалюк, Ю. Н. (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2014)
One of the priorities of arc welding is to improve its performance. The traditional solution to this problem involves increasing the amount of metal per unit of time weld. This is due to the limited capacity of the penetrating arc. However, this increases the attachment of heat in the weld, which adversely affects its quality. To solve this problem requires a fundamentally different approach - an increase in the penetration depth. This can be achieved by increasing the penetrating power of the arc by reducing the diameter of the electrode wire or the use of activating fluxes. Studies indicate that by reducing the diameter of the electrode wire can achieve a substantial increase in the penetration depth. However, the practical implementation of this direction is associated with a number of technical difficulties. The second direction of solving this problem is the development and application of welding consumable electrode activating fluxes by analogy with ATIG-welding.If the penetrating power of the arc when welding in the traditional way to take 1, the use of activating flux can increase it by 2-2.5 times. Therefore, for single full penetration weld metal thickness of 10 mm with the conventional method requires heat input 24694 J/cm. Increase penetrating power of the arc to 2.5 times accompanied by a reduction of heat input required for the base metal thickness of 10 mm to 8103 J/cm.Application of activating flux for welding consumable electrode helps to reduce the length of stay of the weld metal at high temperatures, which has a positive effect on its properties. This is to increase the viscosity of weld metal at low temperatures. Activating fluxes for welding consumable electrode provides increased productivity by 3-4 times compared with traditional technologies. Application of activating fluxes for welding consumable electrode gas shielded welding provides increased performance while reducing its energy consumption and improving the properties of welded joints.